The Impact of Charismatic (Inspirational) Teachers in Building Positive Relationships with Their Students. - Qardaku, Nevila Gurra (European Journal of Multidisciplinary Studies, 2019)
It is emphasized by the relevant literature that the same student engages more in the class of a teacher he /she loves and sincerely cares for and the same student does not engage much in the lesson of a teacher who she hates the student. Lack of feelings of caring of teachers against to students paralyzes learning. Learners learn more when they think the teacher likes them and they like the teacher. The path to the student's mind is through the gain of his heart. The purpose of this research is to research based on reviewing the new relationship between charismatic (inspirational) teachers and building relationships with their students. Based on the studies it was found that; Charismatic teachers (inspirational) give many advantages to building and maintaining positive relationships with all students, and this did not differ from the gender, the school sector or the career phase in which they were inspiring teachers. These teachers are empathetic, understand their students, respond to their needs, promote respect and mutual sympathy, and adapt lessons to the needs of individual students. It was also found that their relationship with students is dynamic and that they invest heavily in these relationships, although their construction requires a lot of effort and an important adaptation period through which teachers know the students and vice versa. Conclusion; charismatic (inspirational) teachers cultivate very positive relationships with their students in the service of teaching development. This study helps teachers and decision-makers in education.376872579794100038633407979410003959225797941000
Keywords: charismatic (inspirational) teachers, empathic, honest care, earning a student's heart, high school students, positive relationship with students.